2005
DOI: 10.1088/0953-2048/18/12/030
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in-field critical currents of YBCO second-generation (2G) wire by Dy additions

Abstract: The addition of dysprosium oxide nanoparticles is shown to improve the critical current in perpendicular magnetic fields for second-generation (2G) wire formed by metal-organic deposition (MOD). Typical enhancements in J c are from 0.17 MA cm −2 to over 0.33 MA cm −2 at 77 K and B perp = 1.5 T. TEM analysis shows that we are introducing (Y, Dy) 2 O 3 nanoparticles with dimensions of 10-50 nm. A simple theoretical analysis shows that the maximum pinning effect for additions is expected at excess concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 15 publications
7
64
1
Order By: Relevance
“…Early work suggested that Dy additions to the MOD films provided significant enhancements in the pinning for Hʈc. [30,103] , respectively) even though the film thicknesses and self-field J c 's were nominally the same.…”
Section: Rare Earth Additions For Flux Pinningmentioning
confidence: 99%
“…Early work suggested that Dy additions to the MOD films provided significant enhancements in the pinning for Hʈc. [30,103] , respectively) even though the film thicknesses and self-field J c 's were nominally the same.…”
Section: Rare Earth Additions For Flux Pinningmentioning
confidence: 99%
“…For films grown by MOD, uncorrelated nanoparticles of Y 2 O 3 [7,11], rare-earth oxides [11][12][13], or BaZrO 3 [11,14,15] have been observed. The introduction of these nanoparticles improves the I c for magnetic-field angles away from the parallel direction, but there can be a reduction in planar pinning.…”
Section: Hts Filmmentioning
confidence: 99%
“…Improvements due to Dy doping in MOD -deposited YBCO fi lms were also reported [21] . High density of nanoparticles of (Y, Dy) 2 O 3 10 -50 nm in diameter along with stacking faults and planar defects were observed, and these were proposed to contribute to enhance pinning [22,23] . Eu -doped PLD fi lms exhibited better magnetic fi eld performance at low fi elds than pure YBCO at different orientations [24] .…”
Section: Rare Earth Dopingmentioning
confidence: 99%